Making Rapid Response Real: Change Management and Organizational Learning in Critical Patient Care - Park, Jason D. (Hamilton Books, 2009)
Rapid Response Teams (RRTs) are a recent innovation in hospitals that makes critical care teams available to a nurse within seconds. When these teams function properly, studies have shown that they can reduce a hospital's mortality rate by almost forty percent. Yet, in spite of the possible benefits, doctors and nurses at hospitals that have committed to adopt RRTs can be reluctant to do so. Making Rapid Response Real discusses a study that identifies several reasons why people in organizations resist this kind of change, and offers recommendations for how leaders can fuel successful adoption of an innovative practice. Applying ideas from sociology and psychology to a management context, Jason D. Park offers research-driven insights for managers in a variety of implementation situations.